2006
DOI: 10.1144/gsl.sp.2006.263.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary and diagenetic environments of the Wildmoor Sandstone Formation (UK): implications for groundwater and contaminant transport, and sand production

Abstract: The Wildmoor Sandstone Formation, proved in three boreholes drilled at Birmingham University, is dominated by fine- to medium-grained sandstones deposited in a braided river environment, within which channel lag, channel fill and abandoned channel facies are recognized. Minor proportions of aeolian sandsheet are present, as are dolocretes, not previously reported in the formation.The sandstones are feldspathic and lithic arenites, and typically are clay-poor. Early dolomite dominates the diagenetic overprint, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…Laboratory measurements indicate that the seams typically have permeabilities of 3-6 orders of magnitude lower than the host sandstone (Fowles & Burley 1994;Ballard 2000;Main et al 2001;Bouch et al 2006). Fowles & Burley (1994) also found that the permeability of the sandstone immediately surrounding the seams is increased (by 3-4 times in the case described).…”
Section: Anti Fracturesmentioning
confidence: 85%
See 3 more Smart Citations
“…Laboratory measurements indicate that the seams typically have permeabilities of 3-6 orders of magnitude lower than the host sandstone (Fowles & Burley 1994;Ballard 2000;Main et al 2001;Bouch et al 2006). Fowles & Burley (1994) also found that the permeability of the sandstone immediately surrounding the seams is increased (by 3-4 times in the case described).…”
Section: Anti Fracturesmentioning
confidence: 85%
“…Not surprisingly, granulation-seam orientations may parallel main slip-surface orientations (e.g. Bouch et al 2006) (Table 3). Reactivation is common, and complex structures can form (Edwards et al 1993).…”
Section: Anti Fracturesmentioning
confidence: 96%
See 2 more Smart Citations
“…However, no calcified root structures or features indicating pedogenesis such rooting are observed at Styrrup, although calcification and evidence of colonization has been described elsewhere in the Sherwood Sandstone (e.g. Bouch et al, 2006;.…”
Section: Channel Element -Chmentioning
confidence: 95%